Peran Pasar Modal dalam Pertumbuhan Ekonomi di Indonesia - Dini Selasi; Puput Indiyani; Siti Jolehah (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
The capital market provides alternative sources of funding and investment facilities for companies that operate based on the principles contained in the capital market. As an important part of the economic ecosystem, the capital market has a significant impact on the level of economic growth of a country. When the level of investment increases, the economic growth of the country also increases. Conversely, a decrease in investment can have a negative impact on economic growth. Funds offered in the capital market through various corporate actions, such as initial public offerings, issuance of new shares, and issuance of bonds, are considered much more efficient than the funds obtained by companies from bank loans each year